Excessive work or addiction to work: workaholism in a Colombian company. Pilot study trough application of DUWAS test (2012)
This paper examines the workaholism phenomenon in different work situations in Colombian company. Workaholism was defined as the individual’s steady and considerable allocation of time to work, which is not derived from external necessities (1). The research studies about workaholics and workaholism have been increasing a lot in the last years (2). Workaholism is an addiction that actually is affecting a lot of people around the world and has serious consequences in personal life, in the community and also in economy. Some of these researches are directed to explore ways to diagnose when a person is workaholic and when this situation may affect the performanceof the individual in work, daily life activities and especially in psychosocial area. Objective: this pilot study contributes to identify if Colombian workers present the main characteristicsof workaholism and if the job they perform is related to the presence of the characteristics of this addiction. Materials and method: for this pilot study used the Dutch Work Addiction Scale(DUWAS), this test suggests when a person has work addiction, trough the evaluation of two main components working excessively and working compulsively. Results: the study find differences for the two groups: the 67% of the AE group are over the average while only the 33% of the members of the O group are over it. Conclusions: these percentages show that the combinations of the components of workaholism are more evident in the population belonging to the administrative/executive jobs group, giving evidence that workaholism is presented in greater proportion in the population performance management positions.